Antigen itself antibody: an alternative one‐step immunoassay for measuring the anti‐idiotypic antibody titer. (September 2014) - Kabir, M. Enamul; Krishnaswamy, Senthilkumar; Selvakumar, Dakshnamurthy; Miyamoto, Masahiko; Furuichi, Yasuhiro; Komiyama, Tadazumi
Abstract Immunoassay designs rely on the great specificity of antibodies and a suitable marker that facilitates generation of a quantitative signal. Currently, there is no reliable method for measuring the titers of an anti‐idiotypic antibody. Our initial attempt to measure titers of mouse anti‐idiotypic antibody after idiotypic vaccination with HM‐1 killer toxin neutralizing monoclonal antibody (nmAb‐KT) failed. Because the injected antigen, nmAb‐KT, is a mouse IgG, using a commercial antibody to measure the antibody titer always gave a false positive signal against control mouse serum antibody in parallel with the antigen‐treated immunized serum antibodies. To get a reliable and clearly differentiable signal by ELISA, idiotypic antigen was labeled with HRP and HRP‐conjugated‐nmAb‐KT used to measure the antibody titers in the antigen‐treated mice. Compared with control mice, signals were found in high anti‐nmAb‐KT IgG responses in test mice; however, untreated control mice had a significant amount of purified non‐specific IgG. This method is amenable to long read lengths and will likely enable anti‐idiotypic antibody titer measurement in a more specific and cost effective way without requiring commercial antibody.